Electromyographical Comparison of Four Common Shoulder Exercises in Unstable and Stable Shoulders. (6th August 2012) - Sciascia, Aaron; Kuschinsky, Nina; Nitz, Arthur J.; Mair, Scott D.; Uhl, Tim L.
Abstract : This study examines if electromyographic (EMG) amplitude differences exist between patients with shoulder instability and healthy controls performing scaption, prone horizontal abduction, prone external rotation, and push-up plus shoulder rehabilitation exercises. Thirty nine subjects were categorized by a single orthopedic surgeon as having multidirectional instability (n = 10 ), anterior instability (n = 9 ), generalized laxity (n = 10 ), or a healthy shoulder (n = 10 ). Indwelling and surface electrodes were utilized to measure EMG activity (reported as a % of maximum voluntary isometric contraction (MVIC)) in various shoulder muscles during 4 common shoulder exercises. The exercises studied effectively activated the primary musculature targeted in each exercise equally among all groups. The serratus anterior generated high activity (50–80% MVIC) during a push-up plus, while the infraspinatus and teres major generated moderate-to-high activity (30–80% MVIC) during both the prone horizontal and prone external rotation exercises. Scaption exercise generated moderate activity (20–50% MVIC) in both rotator cuff and scapular musculature. Clinicians should feel confident in prescribing these shoulder-strengthening exercises in patients with shoulder instability as the activation levels are comparable to previous findings regarding EMG amplitudes and should improve the dynamic stabilization capability of both rotator cuff and scapular muscles using exercises designed to address glenohumeral joint instability.